2005
DOI: 10.1002/mrm.20441
|View full text |Cite
|
Sign up to set email alerts
|

Iopamidol: Exploring the potential use of a well‐established x‐ray contrast agent for MRI

Abstract: Iopamidol is one of the most common contrast media used for diagnostic CT-based clinical protocols. Chemically, this molecule contains two pools of mobile protons (amide and alcoholic) that are in exchange with water. At 7.05 T, pH 7.4, and 312 K, the exchange rate of the alcoholic protons is too fast to affect the NMR properties of water protons, whereas the slowly exchanging amide protons induce a T 2 -shortening effect on the "bulk" water signal that is detectable when the concentration is about 12 mM. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 18 publications
5
132
0
Order By: Relevance
“…Later, our group explored the CEST properties of iopamidol, a small diamagnetic molecule widely used as contrast agent in CT clinical protocols (24). Besides the three iodine atoms necessary for the X-ray detection, iopamidol contains three pseudo-equivalent exchanging amide protons (Dv offset 4.1 ppm).…”
Section: Lmw Diacestmentioning
confidence: 99%
“…Later, our group explored the CEST properties of iopamidol, a small diamagnetic molecule widely used as contrast agent in CT clinical protocols (24). Besides the three iodine atoms necessary for the X-ray detection, iopamidol contains three pseudo-equivalent exchanging amide protons (Dv offset 4.1 ppm).…”
Section: Lmw Diacestmentioning
confidence: 99%
“…Our specific “acidoCEST MRI” protocol measures the two CEST signals produced by the amide protons of iopamidol (Isovue ™ , Bracco Imaging, Inc.), which is FDA-approved for clinical CT studies that we have repurposed for CEST MRI exams [10]. These CEST signals are linearly correlated with pH because the exchange of amide protons and water protons is base-catalyzed [11].…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, it has been shown that iopamidol is suitable for producing MRI contrast by exploiting the chemical exchange saturation transfer (CEST) approach based on the transfer of saturated magnetization to the water resonance via chemical exchange, causing a decrease in the water signal intensity. 6 As originally demonstrated by Ward et al, 7 CEST-MRI is a unique contrast mechanism that is sensitive to contrast media concentration and local properties such as pH and temperature. [8][9][10][11][12][13] Notably, iodinated agents such as iopamidol and iopromide, containing 2 nonequivalent groups of amide protons, allow the setup of a ratiometric procedure for in vivo pH mapping in different tissues and pathological models.…”
mentioning
confidence: 98%